2013
DOI: 10.4103/0019-5545.116315
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and antidepressant effects of yoga

Abstract: Context:Hypercortisolemia is well-known in depression and yoga has been demonstrated earlier to reduce the parameters of stress, including cortisol levels.Aim:We aimed to find the role of yoga as an antidepressant as well as its action on lowering the serum cortisol levels.Settings and Design:An open-labeled study consisting of three groups (yoga alone, yoga along with antidepressant medication and antidepressant medication alone) was conducted at a tertiary care psychiatry hospital.Methodology:Out-patient dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(78 citation statements)
references
References 21 publications
6
71
1
Order By: Relevance
“…Hamilton Depression Rating Scale (HDRS) and serum cortisol level were used to assess the data. The findings of the study proved that yoga has an effect of antidepressant and reduction in the level of cortisol 18 .…”
Section: Discussionmentioning
confidence: 61%
“…Hamilton Depression Rating Scale (HDRS) and serum cortisol level were used to assess the data. The findings of the study proved that yoga has an effect of antidepressant and reduction in the level of cortisol 18 .…”
Section: Discussionmentioning
confidence: 61%
“…Increased parasympathetic activity may cause reduced firing of the paragigantocellular nucleus of the medulla to locus coeruleus, and decreased stimulation of locus ceruleus could reduce norepinephrine output, resulting in relaxation, quiescence, and reduced respiratory and heart rates [30]. Using real-time functional MRI, attempts were made in healthy volunteers to modulate the activation of their own anterior cingulate cortex to alter their pain experience [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies confirmed the physiological effects and advantages of yoga in the treatment of mental illnesses characterized by decrease in cortisol, plasma oxytocin, heart rate variability, increase in neurotropic factors (BDNF), copiousness of the cognitive experience related potential, and gray matter level are also reported [12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%